Transcriptomic and Metabolomic Response to High Light in the Charophyte Alga Klebsormidium nitens - Serrano-Pérez, Emma; Romero-Losada, Ana B.; Morales-Pineda, María; García-Gómez, M. Elena; Couso, Inmaculada; García-González, Mercedes; Romero-Campero, Francisco J. (Frontiers in Plant Science, 2022)
During the evolution of life on Earth, the conquest of land by plants played a pivotal role producing a boost in land biomass, a substantial drop in atmospheric CO2, an increase in oxygen and the emergence of new terrestrial habitats facilitating land colonization by animals. Therefore, the characterization of the molecular mechanisms that allowed plant terrestralization is a cornerstone in evolutionary studies. Viridiplantae or the green lineage is divided into two clades Chlorophyta or green microalgae and Streptophyta that in turn splits into Embryophyta or land plants and Charophyta. The latest are mainly considered aquatic algae although some facultative terrestrial species has been identified. Charophyta are generally accepted as the extant algal species most closely related to current land plants and, therefore, they are used in evolutionary studies on plant terrestralization. High light irradiance was one of the major stressors that ancestral charophytic algae needed to overcome during the transition from aquatic to terrestrial environments. In this study, we have chosen the facultative terrestrial early charophytic alga Klebsormidium nitens to perform an integrative transcriptomic and metabolomic analysis under high light in order to unveil key mechanisms involved in the early steps of plants terrestralization. We found a fast chloroplast retrograde signaling possibly mediated by reactive oxygen species and the inositol polyphosphate 1-phosphatase (SAL1) and 3′-phosphoadenosine-5′-phosphate (PAP) pathways inducing gene expression and accumulation of specific metabolites. Systems used by both Chlorophyta and Embryophyta were activated such as the xanthophyll cycle with an accumulation of zeaxanthin and protein folding and repair mechanisms constituted by NADPH-dependent thioredoxin reductases, thioredoxin-disulfide reductases and peroxiredoxins. Similarly, cyclic electron flow, specifically the pathway dependent on Proton Gradient Regulation 5, was strongly activated under high light. We detected a simultaneous co-activation of the non-photochemical quenching mechanisms based on LHC-like Stress Related protein and the photosystem II subunit S that are specific to Chlorophyta and Embryophyta respectively. Exclusive Embryophyta systems for the synthesis, sensing and response to the phytohormone auxin were also activated under high light in Klebsormidium leading to an increase in auxin content with the concomitant accumulation of amino acids such as tryptophan, histidine and phenylalanine.